In vitro chemotherapy for inducing tolerance towards Tomato leaf curl New Delhi virus (ToLCNDV) in bitter gourd (Momordica charantia L.) - Adarsh, M V; Smitha, B; Soni, K B; Swapna, A; Ayisha, R; Manjushri, D D (Plant Science Today, 2025)
ToLCNDV, a whitefly transmitted begomovirus, is reported to be associated with Bitter gourd yellow mosaic disease (BGYMD), a deadly disease in bitter gourd that can lead to 100 % loss of marketable fruits. The aim of the study was to evaluate the effect of in vitro treatment with antiviral compounds for developing tolerance towards ToLCNDV in bitter gourd. Germinated seeds of bitter gourd were grown for 14 days in Murashige and Skoog (MS) medium supplemented with 2 ppm Benzyladenine (BA) and antiviral compounds viz. ribavirin (Treatment 1), Virus-Ex (Treatment 2) and extracts of Bougainvillea spectabilis (Treatment 3). Plants grown in MS medium supplemented with 2 ppm BA were used as control. The treated plants were hardened in coir pith compost and whitefly-mediated artificial inoculation of the virus was carried out 2 weeks after hardening. Absence of virus in treatment 1 and treatment 2 was confirmed in PCR using universal Deng primer. Biometric observations of treated plants (35-day-old) viz. plant height, number of leaves and leaf area were found higher in all the treatments compared to control, out of which treatment using ribavirin was found to be highly significant for all the parameters.